A characterization of the family of iterated nonexpansive mappings under every renorming - Pérez-García, Víctor; Castillo-Santos, Francisco Eduardo (Topological Methods in Nonlinear Analysis, 2024)
We characterize the family of iterated nonexpansive mappings thatare stable under every renorming. The family of iterated nonexpansivemappings contains the family of nonexpansive mappings, it also containsquasi-nonexpansive and Suzuki's (C)-type mappings with fixed points,among others. We also give the corresponding characterizations forquasi-nonexpansive and some Suzuki's (C)-type mappings with fixed points.